Pengaruh Penggunaan Media Pembelajaran Quizizz Terhadap Motivasi Belajar Siswa Kelas V - andi nurfaisah; Andi Amparita Said; Nurlaela Latif (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to find out whether there is an effect of using Quizizz learning media on the learning motivation of fifth grade students at SDN 3 Lemba, Soppeng Regency. This study uses a quantitative research approach with the type of experimental research using a True Experimental Design research design. The results showed that there were differences in students' learning motivation between the experimental class and the control class. Then continued with the N-Gain test, the N-Gain Score for the experimental class was 0.4 in the medium category and the N- Gain Score for the control class was 0,2 is in the low category. It can be concluded that the use of quizizz learning media has a significant effect on the learning motivation of fifth grade students at SDN 3 Lemba, Soppeng Regency